Ranibizumab versus Aflibercept in Macular Edema Secondary to Retinal Vein Occlusion in Real Life: A Retrospective Case Control Study - Abdullah Özkaya (Beyoglu Eye Journal, 2017)
INTRODUCTION[|]The present study is comparison of efficacy of ranibizumab and aflibercept in the treatment of macular edema (ME) secondary to retinal vein occlusion (RVO) in real life.[¤]METHODS[|]Design was retrospective, case-control study. Treatment naïve RVO patients with ME who were treated with ranibizumab or aflibercept and had minimum follow-up time of 6 months were included. Primary outcome measures were changes in best corrected visual acuity (BCVA) and central retinal thickness (CRT). Secondary outcome measure was number of injections administered.[¤]RESULTS[|]Mean baseline, month 3, and month 6 BCVA in ranibizumab group was 0.95+-0.61-, 0.50+-0.30-, and 0.66+-0.58 logarithm of the minimum angle of resolution (LogMAR), respectively. Mean baseline, month 3, and month 6 BCVA in aflibercept group was 0.85+-0.65-, 0.61+-0.58-, and 0.65+-0.55 LogMAR, respectively. Mean baseline, month 3, and month 6 CRT in ranibizumab group was 598+-189-, 473+-162-, and 359+-134 μm, respectively. Mean baseline, month 3, and month 6 CRT in aflibercept group was 512+-141-, 345+-154-, and 374+-172 μm, respectively. Mean number of injections was 2.7+-0.8 for ranibizumab group, and 2.2+-1.0 for aflibercept group (p=0.08).[¤]DISCUSSION AND CONCLUSION[|]Ranibizumab and aflibercept are both effective agents in the treatment of ME secondary to RVO. Visit and injection figures were lower than those reported in prospective, multicenter studies, as expected, but functional and anatomical outcomes were comparable.[¤]